Speciation of heavy metals by modified BCR sequential extraction procedure in different depths of sediments from Sungai Buloh, Selangor, Malaysia - Nemati, K.; Bakar, N.K.A.; Abas, M.R.; Sobhanzadeh, E. (2011)
The sequential extraction procedure proposed by the European Standard, Measurements and Testing (SM&T) program, formerly the Community Bureau of Reference (BCR), was applied for partitioning of heavy metals (HMs) in river sediments collected along the course of Sungai Buloh and the Straits of Malacca in Selangor, Malaysia. Eight elements (V, Pb, Cd, Cr, Co, Ni, Cu and Zn) from seven stations (S1-S7) and at different depths were analyzed using the modified BCR Sequential Extraction Procedure (SEP) in combination with ICP-MS to obtain the metal distribution patterns in this region. The results showed that heavy metal contaminations at S2 and S3 was more severe than at other sampling sites, especially for Zn, Cu, Ni and Pb. Nevertheless, the element concentrations from top to bottom layers decreased predominantly. The samples from the Straits of Malacca (S4-S7) the highest contamination factors obtained were for Co, Zn and Pb while the lowest were found for V and Cr, similar to Sungai Buloh sediments. The sediments showed a low risk for V, Cr, Cu and Pb with RAC values of less than 10, but medium risk for Co, Zn (except S3), Cd at S1 and S2 and Ni at S1, S3 and S5. Zn at S3 and Cd at S3-S7 showed high risk to our sediment samples. There is not any element of very high risk conditions in the selected samples.